2000
DOI: 10.1177/096368970000900404
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Intrathecal Immune Response in Amyotrophic Lateral Sclerosis Patients Implanted with Encapsulated Genetically Engineered Xenogeneic Cells

Abstract: A phase I/II clinical trial has been performed in 12 amyotrophic lateral sclerosis (ALS) patients to evaluate the safety and tolerability of intrathecal implants of encapsulated genetically engineered baby hamster kidney (BHK) cells releasing human ciliary neurotrophic factor (CNTF). These patients have been assessed for a possible intrathecal or systemic immune response against the implanted xenogeneic cells. Hundreds of pg CNTF/ml could be detected for several weeks in the cerebrospinal fluid (CSF) of 9 out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(20 citation statements)
references
References 40 publications
0
19
0
1
Order By: Relevance
“…Encapsulation is a promising approach to reduce the risks and complications associated with cellular therapies in the central nervous system: In a first phase I clinical trial in ALS to assess safety and tolerability of encapsulated genetically engineered baby hamster kidney (BHK) cells releasing human ciliary neurotrophic factor (CNTF), therapeutic levels of the secreted peptide could be detected for several weeks without limiting side effects [37]. A phase I/II clinical trial confirmed the safety and tolerability of intrathecal implants of these cell capsules, with signs of only a very mild humoral immune response [38]. Studies in experimental animal models using the same cell capsules as in the present study showed complete prevention of any immune response by microencapsulation of cells prior to transplantation [21], [24].…”
Section: Discussionmentioning
confidence: 99%
“…Encapsulation is a promising approach to reduce the risks and complications associated with cellular therapies in the central nervous system: In a first phase I clinical trial in ALS to assess safety and tolerability of encapsulated genetically engineered baby hamster kidney (BHK) cells releasing human ciliary neurotrophic factor (CNTF), therapeutic levels of the secreted peptide could be detected for several weeks without limiting side effects [37]. A phase I/II clinical trial confirmed the safety and tolerability of intrathecal implants of these cell capsules, with signs of only a very mild humoral immune response [38]. Studies in experimental animal models using the same cell capsules as in the present study showed complete prevention of any immune response by microencapsulation of cells prior to transplantation [21], [24].…”
Section: Discussionmentioning
confidence: 99%
“…Cell encapsulation overcomes these issues by delivering therapeutic molecules directly to the brain area of interest (Box 1). Initial clinical trials for amyotrophic lateral sclerosis (ALS) and Huntington's disease (HD) [68][69][70] were based on solid preclinical data showing that encapsulated cells could be configured into implantable capsules that were biocompatible, maintained cell viability for extended periods of time, and were functional in animal models. However, during Phase I clinical trials, it became evident that obstacles remained.…”
Section: Encapsulated Cells For Neurological Diseasesmentioning
confidence: 99%
“…This system, in the current iteration which provides sustained release of VEGF for 2-3 weeks, though would likely not provide delivery long enough to justify its clinical use in a chronic disease such as HD. Still, several approaches are being evaluated both pre-clinically and clinically that might be suitable for delivery of VEGF or other molecules on the order of years to the CNS (Zurn et al 2000;Bloch et al 2004;Yasuhara and Date 2007;Marks et al 2008). The angiogenic effects of VEGF have been well documented, but its role in neuroprotection is becoming increasingly clear.…”
Section: Discussionmentioning
confidence: 99%